(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: This in vivo study was done to correlate the values of three different electronic apex locators: Root ZX II, iPex II, and Raypex 6, with the radiographic working length (WL). Materials and Methods: Nineteen maxillary incisors with completely formed root apices indicated for endodontic treatment were chosen. After access preparation, coronal flaring and pulp extirpation, electronic measurement of WL was done with a No: 15 K-file using the three devices on each tooth. A WL radiograph was then taken with the file placed within the canal and the length determined by following Ingle’s method. The data were then analyzed using the correlation coefficient and Z-test. Results: Root ZX II showed the maximum correlation (r = 0.9881) with radiographic WL followed by Raypex 6 (R = 0.9731) and iPex II (R = 0.9508). Root ZX II had a statistically significant higher correlation with radiographic WL in comparison with iPex II (P < 0.05). Conclusion: Maximum correlation of readings with the radiographic length was shown by Root ZX II followed by Raypex 6 and then by iPex II.